The Staunton Shakespeare, Volume 1 - Shakespeare, William (Cambridge library collection. Literary Studies, 1858)
First published in 1858, this is the first of three volumes of Howard Staunton's collection of Shakespeare's plays, with black-and-white illustrations by the prolific artist John Gilbert. Staunton's annotated edition, based on the folio and quarto editions collated with the texts of later editors from Rowe to Dyce, combines common sense with meticulous research, making it a definitive resource in its day. Each play is accompanied by an introduction giving details of its original production and publication and the sources of its plot, critical commentary, and footnotes explaining terms and expressions. This volume contains The Two Gentlemen of Verona, Love's Labour's Lost, The Comedy of Errors, Romeo and Juliet, The Taming of the Shrew, King John, A Midsummer Night's Dream, The Merchant of Venice, King Richard II, King Henry IV Part 1, King Henry IV Part II, The Merry Wives of Windsor, and Much Ado About Nothing